Mechanism of the administrative adjusting of activity of corporations in Ukraine - Гончарук, Степан Тихонович; Нашинець-Наумова, Анфіса Юріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The article is devoted research of concept of mechanism of the administrative adjusting of activity of corporations in Ukraine and him basic structural elements taking into account the specific of public relations in the field of activity of corporations on the settlement of which they are directed.